The Role of Information and Communication Technology (ICT) in Advancing Smart Living: A Systematic Literature Review - Mashudah Sabilaturrizqi; Moh Faizal Akbar (G-Tech: Jurnal Teknologi Terapan, 2026)
The rapid growth of Information and Communication Technology (ICT) has given rise to the Smart Living paradigm, which integrates digital devices, services, and infrastructure to enhance the living standard. Using the PRISMA framework and a Systematic Literature Review (SLR) technique, this study aims to identify how ICT supports smart living. Literature searches were conducted on six reputable international databases (ScienceDirect, IEEE Xplore, Emerald Insight, SpringerLink, Wiley Online Library, and Taylor & Francis Online) with publications ranging from 2020 to 2025. From 1,580 articles, a gradual screening process yielded 30 relevant articles for analysis. The synthesis results show that the artificial intelligence (AI) and Internet of Things (IoT) are the dominant technologies in supporting automation, energy management, digital health services, and community participation. The implementation of ICT has a positive impact on improving quality of life, energy efficiency, new business models, and environmental sustainability. However, challenges such as data privacy, the digital divide, and implementation costs still need attention. This study maps technology trends and innovation opportunities for the development of an inclusive and sustainable Smart Living ecosystem. This review contributes an ICT-centric technology-to-impact mapping for Smart Living and highlights actionable research gaps for inclusive and sustainable implementation.